Shape Optimization of the Muffler Shield with Regard to Strength Properties - JAROSZ, Joachim; DŁUGOSZ, Adam (Engineering Transactions, 2023)
This paper is devoted to the shape optimization of the muffler shield with regard to strength properties. Three different optimization criteria are defined and numerically implemented concerning the strength properties of the shield, and different variants of optimization tasks are solved using both built-in optimization modules and in-house external algorithms. The effectiveness and efficiency of the optimization methods used are compared and presented.